Acoustic radiation force impulse imaging for non‐invasive assessment of liver fibrosis in chronic hepatitis B. Issue 4 (31st July 2012) - Friedrich‐Rust, M.; Buggisch, P.; de Knegt, R. J.; Dries, V.; Shi, Y.; Matschenz, K.; Schneider, M. D.; Herrmann, E.; Petersen, J.; Schulze, F.; Zeuzem, S.; Sarrazin, C.
Summary: Acoustic radiation force impulse (ARFI) imaging is a novel ultrasound‐based elastography method that is integrated in a conventional ultrasound machine. It might provide an alternative method to transient elastography for the noninvasive assessment of liver fibrosis. While previous studies have shown comparable diagnostic accuracy of ARFI to transient elastography in chronic hepatitis C, the aim of the present prospective multicenter study was to evaluate ARFI for the assessment of liver fibrosis in chronic hepatitis B. ARFI imaging involves the mechanical excitation of tissue using short‐duration acoustic pulses to generate localized displacements in tissue. The displacements result in shear‐wave propagation which is tracked using ultrasonic, correlation‐based methods and recorded in m/s. In the present international prospective study, patients infected with chronic hepatitis B received ARFI imaging, blood tests and if available transient elastography. The results were compared to liver biopsy as reference method analysed by a central pathologist. In 92 of 114 patients, a comparison of ARFI with transient elastography was possible. ARFI imaging and transient elastography correlated significantly with histological fibrosis stage. The diagnostic accuracy expressed as areas under ROC curves for ARFI imaging and transient elastography was 0.75 and 0.83 for the diagnosis of significant fibrosis ( F ≥ 2), 0.93 and 0.94 for the diagnosis of severe fibrosis ( F ≥ 3), and 0.97 and 0.93 for the diagnosis of liver cirrhosis, respectively. No significant difference was found between ARFI and transient elastography. ARFI imaging is a reliable ultrasound‐based method for the assessment of advanced stages of liver fibrosis in chronic hepatitis B.